Pemanfaatan Saluran Whatsapp Terhadap Kepuasan Literasi Masyarakat Informasi di Kabupaten Tangerang - Hamzah, Syahrial; Aditya, Toddy; El Yana, Korry (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This research aims to find out how useful the WhatsApp channel is for people's literacy satisfaction in Tangerang Regency. The research method applied in this research is the Systematic Literature Review (SLR) method using the Vosviewer application, with variable x, namely the use of WhatsApp channels using the UTAUT theory and variable y, literacy satisfaction using the uses and gratification theory. The results of the research reveal that the WhatsApp channel can satisfy the literacy of the information community in Tangerang Regency with this channel feature helping the community, especially the information community, especially to satisfy their literacy desires. The results of this research contribute to the existing channels in the WhatsApp application. The limitation of this research is that the data used is still limited to the type of secondary data, namely previous articles sourced from dimensions. Future research needs to use primary data, namely interview and observation data.